THE USE OF DIGITAL TECHNOLOGIES IN FACILITATING ENGLISH LANGUAGE LEARNING AMONG UNDERGRADUATE STUDENTS - Tulung, Golda Juliet; Sebayang, F Ari Anggraini; Conny Lasut, Theresia Maria; Larope, Billy Christian (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
With the prevalent and ubiquotous exposure to the Internet and digital technologies, students obtain better opportunities to various learning sources. This study explored how undergraduate students utilized digital technologies to facilitate their learning in an informal setting. The study employed a qualitative design, with interview as the instrument of data collection. A total of 10 undergraduate students in English Department, Faculty of Humanities at Sam Ratulangi University, participated in the study. The interview questions were formulated by using the theory of self-regulated learning, including preparing learning environment, organizing material, and monitoring and evaluation. While the students utilized the digital technology within their study, the use was still inconsistent, as they had limited knowledge about using the learning aids effectively. The results also revealed that the students did not set specific learning goals and select appropriate technologies to assist them during their study. Additionally, the results also suggested that the students did not monitor and use digital technologies to evaluate and monitor their learning. This study highlights the needs for educators to promote the incorporation of digital technologies in improving the quality of learning among students for a sustainable and independent learning.